Dissolution characteristics of selected fruit tablets with effervescent agents (pdf symbol pada muka surat references) - Saifullah, Md. (2015)
Tableting of fruit powder is a unique technique in the area of fruit powder preservation. Dissolution characteristic of tablet is an important parameter for quality control and production. The acceptability and popularity of fruit powder tablet depend on its dissolution rate. Physicochemical properties of tablet ingredients have great influence on dissolution behaviour of tablet. This research was conducted in two major areas namely determination of physicochemical properties of fruit powder and their relationship with the dissolution of tablet with effervescent agents, and dissolution profiling of fruit powder effervescent tablets and dissolution profile comparison. Pitaya, pineapple, mango and guava fruits were used in this research, as these fruits are grown in large quantity in Malaysia. Tablets with 20 mm diameter and 2.5 gm weight were made by using a direct compression method at a constant pressure via a universal testing machine. Dissolution test was carried out in a dissolution tester and dissolved amount of solute was measured by an Ultraviolet spectrophotometric test as a function of time. Distilled water and simulated saliva was used as dissolution medium in the dissolution test at room temperature and 37oC temperature respectively. The investigation on physicochemical analysis showed that fruit powders were different from each other in terms of physical and chemical properties. The results showed that the fat content in powder has inverse relationship with dissolution rate. On the other hand, porosity of the tablet represented proportional relationship with dissolution rate and application of effervescent agents increased the dissolution rate of tablet significantly. In this study three types of method were adopted to compare the dissolution profile which includes model dependent, model independent and statistical method. Five release kinetics mathematical equations were used to compare dissolution profile in model dependent method. According to model dependent method, when distil water was used as dissolution medium, pineapple, guava and mango powder tablet dissolution profile shows similarity as their dissolution profile was fitted with Higuchi model. However, pitaya powder tablet dissolution profile was different from other types as its dissolution profile was fitted very well with zero order kinetics model. In simulated saliva, same phenomenon was appeared; pineapple, guava and mango powder tablet dissolution profile shows similarity and pitaya powder tablet dissolution profile was different from them. On the other hand, according to model independent method, dissolution profiles of fruit powder tablets were in the similarity range at most of the points. However, in the statistical method pair-t test showed that there was significantly difference among the dissolution profile of fruit powder tablets at the level of P<0.01. Based on this study, a better understanding about physicochemical properties of fruit powder and their relationship with dissolution rate and effect of effervescent agents on dissolution rate are obtained, which are essential for processing and handling of fruit powder and tablet preparation as well as improvement of dissolution rate. In conclusion, dissolution profiling and its comparison will be helpful for further change in formulation, development of new formulation, scale up of the production, and quality control in production line during industrial scale production.